1982
DOI: 10.1159/000176556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Proteins on Cholesterol Metabolism in Growing Rats Fed Atherogenic Diets

Abstract: Weanling rats were fed atherogenic diets containing 2% cholesterol and 0.5% bile acids for 4 weeks. The experimental diets contained 10% protein derived from soy protein, wheat gluten, or wheat gluten supplemented with lysine and threonine. The control diet contained 10% protein derived from casein. Rats fed the plant proteins were found to have lower serum cholesterol and triglyceride levels, no detectable amounts of low density lipoprotein, a smaller amount of very low density lipoprotein and a higher concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…This may be true in experimental rats fed H 2 O 2 which exhibited higher TC and LDL compared to that of that of normal group although, the increment were not significantly different. It was well known that dietary fiber, fat, and protein influence plasma cholesterol levels in experimental animals (Mokady and Liener, 1982; Bravo and others 1995; Guillon and Champ, 2000). However, the influence of polyphenols in foodstuffs on the serum lipid levels has not been fully examined (Igarashi and others 1990).…”
Section: Resultsmentioning
confidence: 99%
“…This may be true in experimental rats fed H 2 O 2 which exhibited higher TC and LDL compared to that of that of normal group although, the increment were not significantly different. It was well known that dietary fiber, fat, and protein influence plasma cholesterol levels in experimental animals (Mokady and Liener, 1982; Bravo and others 1995; Guillon and Champ, 2000). However, the influence of polyphenols in foodstuffs on the serum lipid levels has not been fully examined (Igarashi and others 1990).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that proteins derived from plant-origin, such as soybean, sunflower, rice, spinach and radish protein isolates (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), produce activity to maintain lower serum cholesterol concentrations as compared to those of animal proteins such as casein. These reports suggest that some other plant proteins may also have hypocholesterolemic activity; however, the influence of vegetable proteins which are consumed daily on the serum and liver lipid levels has not yet been fully examined.…”
mentioning
confidence: 99%
“…It is well known that plasma cholesterol level in human and several experimen tal animals is affected by dietary proteins, and especially, plant proteins such as soybean protein isolate (1)(2)(3)(4)(5), sunflower seed protein isolate (6), potato protein (7), and wheat gluten (8,9) exert hypocholesterolemic effect as compared with animal protein such as casein. Cho et al reported that leaf protein isolates, prepared by heating green juice from Italian ryegrass and alfalfa, exert hypocholesterolemic effect in rats (10).…”
mentioning
confidence: 99%